THERMAL COMFORT MODEL DEVELOPMENT FOR OFFICE BUILDINGS WITH HYBRID DOWNDRAFT EVAPORATIVE COOLERS IN BAYERO UNIVERSITY KANO - USMAN HARUNA, IBRAHIM; AHMAD RUFAI, IBRAHIM; BALARABE YAHAYA, DALHATU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The numerous thermal comfort models developed for air-conditioned and free-running spaces are unsuitable for accurate prediction of thermal comfort of buildings equipped with hybrid downdraft evaporative cooling (HDEC) systems. This study attempts to develop a thermal comfort model for office buildings equipped with the HDEC in the new campus of Bayero University Kano. The windows of the office buildings were optimized using Taguchi analysis. The 3D model of the baseline office building using the optimum window-to-wall ratio (WWR) of 25% was developed and numerically analyzed using DesignBuilder CFD simulation. The numerical PMVopt results were employed for training the thermal comfort model using the statistical software package Minitab 19. The validation shows a good agreement between the predicted results and the experimental data. The developed model could help building designers and engineers to make appropriate decisions at design stage regarding the thermal comfort of office buildings to be equipped with the HDEC systems.